Lewis pair polymerization of alkyl methacrylate by amidinato silicon compounds and Tris(pentafluorophenyl)borane - Chia, Cher-Chiek (2022)
0.5 mol% of the amidinato disilyne [LSi:]2 (1, L = PhC(NtBu)2) and 1 mol% of B(C6F5)3 cooperatively polymerized methyl methacrylate (MMA) to form poly(MMA) with the H and CH2C(=CH2)COMe end groups (P1, Mn = 3.1 ×103 gmol-1; repeating unit, n = 31; polydispersity index, Đ: 1.55). The catalytic mechanism is proposed, where compound 1 could react with MMA and B(C6F5)3 to form a zwitterionic active species [LSi{CH2C(Me)=C(OMe)O}B(C6F5)3]2. The latter could activate MMA molecules affording poly(MMA) chains on the silicon centers. The methyl group of the last enolate of a poly(MMA) chain on a silicon center could then react with the Si-C bond of the adjacent poly(MMA) chain to form P1, as well as regenerate compound 1 and B(C6F5)3. When compound 1 was replaced by the amidinato amidosilylene [LSiN(SiMe3)2] (2), 1 mol% of compound 2 and 1 mol% of B(C6F5)3 mediated living MMA polymerization in toluene to form the poly(MMA) P2 (Mn = 1.04 ×104 gmol-1; Đ: 1.97).